2020
DOI: 10.1177/1010539520960987
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parity and the Age at Menopause and Menopausal Syndrome in Northwest China

Abstract: This study evaluated the relationships between parity and the age at menopause and menopausal syndrome among Chinese women in Gansu. A total of 7236 women aged 40 to 55 years met study eligibility criteria. The modified Kupperman Menopausal Index scale was used to assess the severity of menopausal syndrome. Cox regression was applied to estimate hazard ratio and 95% confidence interval, and logistic regression was performed to calculate odds ratio and confidence interval. The mean age at menopause was 47.91 ± … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
3
9
0
2
Order By: Relevance
“…The findings of the current study agree with the results of earlier studies reporting that nulliparity was associated with menopausal symptoms 29-32 . Our study showed that nulliparous women were more likely to experience menopausal symptoms compared with those having one or two births, which was consistent with a recent cross-sectional study conducted in Northwest China indicating that women with nulliparity appeared to have higher risks of menopausal syndrome 29 . Compared with women having one or two births, nulliparous women in our study were less likely to have regular physical activity, and reported lower levels of average monthly household income.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of the current study agree with the results of earlier studies reporting that nulliparity was associated with menopausal symptoms 29-32 . Our study showed that nulliparous women were more likely to experience menopausal symptoms compared with those having one or two births, which was consistent with a recent cross-sectional study conducted in Northwest China indicating that women with nulliparity appeared to have higher risks of menopausal syndrome 29 . Compared with women having one or two births, nulliparous women in our study were less likely to have regular physical activity, and reported lower levels of average monthly household income.…”
Section: Discussionsupporting
confidence: 93%
“…[29][30][31][32] Our study showed that nulliparous women were more likely to experience menopausal symptoms compared with those having one or two births, which was consistent with a recent cross-sectional study conducted in Northwest China indicating that women with nulliparity appeared to have higher risks of menopausal syndrome. 29 Compared with women having one or two births, nulliparous women in our study were less likely to have regular physical activity, and reported lower levels of average monthly household income. However, our findings differ from results in SWAN, which found that nulliparous women had lower odds of menopausal symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…An increase in duration of breastfeeding might have an effect on the period of lactating amenorrhea, resulting in a probable delay in reaching menopause (Dasgupta & Ray, 2009). On the other hand, a recent study on North West Chinese women found no relationship between parity and age at menopause (Sun et al, 2021). Several worldwide researches revealed a high prevalence of early menopause in nulliparous women, while an Indian study found that multiple parity was associated with a higher prevalence and earlier onset of menopause (Mozumdar & Agrawal, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Kết quả này cũng phù hợp với Lê Thanh Bình (Hải Phòng-2014), tuổi mãn kinh trung bình trong nghiên cứu của tác giả là 49,26 tuổi [1], Nguyễn Đình Phương Thảo (Huế-2017) là 49,47 [5]. Tuổi mãn kinh trung bình trong nghiên cứu của chúng tôi nằm trong dao động tuổi mãn kinh trung bình ở các nước Châu Á từ 47-50 tuổi: Singapore là 49 tuổi [7], Trung Quốc là 47,91 tuổi [10]. Tuy nhiên, tuổi mãn kinh trung bình của mẫu nghiên cứu thấp hơn so với các nước phát triển: Ở trung tâm Massachusetts-Mỹ; tuổi mãn kinh tự nhiên trung bình là 52,6 tuổi và ở Tây Ban Nha là 51,7 tuổi [9].…”
Section: Bàn Luậnunclassified